Zebrafish teratogenicity test with metabolic activation (mDarT): effects of phase I activation of acetaminophen on zebrafish Danio rerio embryos - Weigt, Stefan; Braunbeck, Thomas (Toxicology, 2010)
The zebrafish Danio rerio embryo test with metabolic activation (mDarT) was developed to assess the teratogenic effects of proteratogens. In this study induced rat liver microsomes (RLM) were used as a mammalian metabolic activation system (MAS), since they contain various cytochrome P450 (CYP) isoforms at high concentrations. Acetaminophen (APAP) is considered not to be teratogenic in vivo, however, in vitro teratogenic effects were observed, e.g. in rat whole embryo culture. The CYP2E1 activation of APAP to the reactive metabolite N-acetyl-p-benzoquinone imine (NAPQI) mainly occurs, when the glucuronidation and sulfatation pathways are saturated. In vivo the soft electrophile NAPQI is usually inactivated by hepatic reduced glutathione (GSH), a soft nucleophile. In this study, we investigated the teratogenic and lethal effects of APAP after CYP activation in zebrafish embryos. In the test groups with APAP and metabolic activation 11.7 ± 7.6% (2 mM), 25.0 ± 8.7% (4 mM) and 50.0 ± 21.8% (6 mM) affected embryos were seen, reaching statistical significance at 4 mM APAP. When embryos were exposed to 6 mM APAP, MAS and 3 mM GSH the percentage of affected embryos decreased to 6.7 ± 5.8%. In contrast teratogenic and lethal effects of metabolically activated cyclophosphamide (CPA) could not be prevented by GSH addition, because the CPA metabolites are strong electrophiles, which preferentially bind to hard nucleophiles like DNA and RNA. The teratogenic and lethal effects of metabolically activated APAP observed in zebrafish embryos with our mDarT standard protocol could be explained by the lack of GSH as a detoxifying system. By adding GSH it was possible to mimic the situation in mammals and thus avoid teratogenic effects in zebrafish embryos.